2013
DOI: 10.1039/c3nr02845c
|View full text |Cite
|
Sign up to set email alerts
|

Tuning nanostructure of graphene oxide/polyelectrolyte LbL assemblies by controlling pH of GO suspension to fabricate transparent and super gas barrier films

Abstract: A technique of layer-by-layer (LbL) self-assembly was used to prepare transparent multilayered gas barrier films consisting of graphene oxide (GO)/branched poly(ethylenimine) (BPEI) on a poly(ethylene terephthalate) substrate. The effect of the GO suspension pH on the nanostructure and oxygen barrier properties of the GO/BPEI film was investigated. The oxygen barrier properties of the assemblies were shown to be highly dependent on the pH. It was demonstrated that the film assemblies prepared using a GO suspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(80 citation statements)
references
References 62 publications
3
75
2
Order By: Relevance
“…The absorbance values of the self-assembled films prepared at three different voltages all showed a linear increase with the number of bilayers. This trend is consistent with that reported in previous studies [36] . Our results indicated that LBL self-assembly is a stacking-growth process at a constant rate under an applied electric field.…”
Section: Multilayer Membrane Preparationsupporting
confidence: 95%
“…The absorbance values of the self-assembled films prepared at three different voltages all showed a linear increase with the number of bilayers. This trend is consistent with that reported in previous studies [36] . Our results indicated that LBL self-assembly is a stacking-growth process at a constant rate under an applied electric field.…”
Section: Multilayer Membrane Preparationsupporting
confidence: 95%
“…As shown in Fig. 3d, no nanopores exist on (GE/GO) 1 /H-PAN membrane surface, due to the micrometer-scale size of GO along horizontal direction, as well as the even spreading and packing of GO on membrane surface resulting from the appropriate pH condition [22]. As a result, the required deposition cycle number for fabricating defect-free layer is reduced, thus greatly simplifying the membrane fabrication procedure.…”
Section: Surface Morphology and Thickness Of Hybrid Multilayer Membranesmentioning
confidence: 97%
“…The combination of above factors leads to The effect of pH value during self-assembly process on membrane separation performance was investigated as listed in Table 1. When the pH value of GE solution and GO dispersion is 2.0, the lower charge density on GO leads to aggregation [22], which results in the uneven spreading and packing of GO and decreases the interaction sites between GE and GO. Furthermore, the subsequent deposition of GE is also influenced with uneven deposition and decreased deposition amount.…”
Section: Surface Morphology and Thickness Of Hybrid Multilayer Membranesmentioning
confidence: 98%
See 1 more Smart Citation
“…It was noticed that a graphene/polymer assembly could provide a tightly packed architecture with insufficient gas diffusion channels 80. Chen et al employed similar methods to construct gas barrier films using GO/PEI multilayered structures and demonstrated that both the pH for the GO suspension and the GO/PEI bilayer number had great influence on the oxygen barrier performance for the multilayered film,81 implying the intercalated structures of tightly oriented and stacked GO/PEI system. Enhanced mechanical properties were also reported by Grunlan and co‐workers for a PAA/PVP‐G system.…”
Section: Self‐assembled Graphene‐based Hybrid Structuresmentioning
confidence: 99%